Metal-Chloride-Activated Empty Fruit-Bunch Carbons for Rhodamine B Removal - Zaini Muhammad Abbas Ahmad; Shaid Mohd Shafiq Mohd (Hungarian Journal of Industry and Chemistry, 2016)
This study aimed to investigate the adsorptive ability of activated carbons derived from empty boil palm fruitbunch carbons through metal-chloride activation. The derived activated carbons were characterized in terms of yield, pH, surface functional groups, and specific surface area. Rhodamine B dye was used as a pollutant probe to evaluate the performance of activated carbons. Results show that empty, ZnCl2-activated fruit-bunch carbon exhibits a higher surface area of 866 m2 g-1 and a Rhodamine B removal yield of 105 mg g-1. Activation at the same temperature of 600 °C using the recovered FeCl2 yields an activated carbon with nearly twice the surface area compared to the fresh one. A direct correlation was obtained between the roles of the specific surface area and removal of Rhodamine B. Empty fruit-bunch carbon is a promising adsorbent precursor for colour removal from water.